Sleeping Habits and Perception of Its Health Effects among College Students (International Journal of Studies in Nursing, 2017)
Inadequate sleep has detrimental effects on both students’ health and academic performance. While college students may know this information, they often do not prioritize sleep above other responsibilities of college life nor perceive their own health as being threatened. The purpose of this quantitative, descriptive study was to determine the sleeping habits and perception of its health effects among college students. In this study, 116 college students in the Midwestern United States were surveyed. Participants completed a demographic and a 19-item Likert-type survey about their sleep habits and their perception of its health effects. In this study, 61% of participants reported obtaining at least an average of 7 hours of sleep per night. In addition, 77% of the participants reported taking naps during the day, with 51% of the naps lasting at least an hour. By comparing the participants’ sleeping habits with the review of the literature, it was concluded that overall, participants did not have beneficial sleeping habits. The majority of the participants (M=3.49; SD=0.57 on a 4- point Likert-type scale), agreed that academics are affected because of the lack of sleep. In conclusion, college students do not have beneficial sleeping habits.